3
$\begingroup$

This is the question:

Use the integral test to determine the convergence of $\sum_{n=1}^{\infty}\frac{1}{1+2n}$.

I started by writing:

$$\int_1^\infty\frac{1}{1+2x}dx=\lim_{a \rightarrow \infty}\left(\int_1^a\frac{1}{1+2x}dx\right)$$

I then decided to use u-substitution with $u=1+2n$ to solve the improper integral. I got the answer wrong and resorted to my answer book and this is where they went after setting $u=1+2n$:

$$\lim_{a \rightarrow \infty}\left(\frac{1}{2}\int_{3}^{1+2a}\frac{1}{u}du\right)$$

And the answer goes on...

What I can't figure out is where the $\frac{1}{2}$ came from when the u-substitution began and also, why the lower bound of the integral was changed to 3.

Can someone tell me?

$\endgroup$
4
$\begingroup$

$$u=1+2x\Longrightarrow du=2dx\Longrightarrow dx=\frac{1}{2}du$$

Remember, not only you substitute the variable and nothing more: you also have to change the $\,dx\,$ and the integral's limits: $$u=1+2x\,\,,\,\text{so}\,\, x=1\Longrightarrow u=1+2\cdot 1 =3$$

$\endgroup$
  • $\begingroup$ Oh yes, I forgot that you have to change the limits of integration when u-substituting to the u-substitution limits of integration. $\endgroup$ – ODP Aug 28 '12 at 16:07
3
$\begingroup$

You have $\int_{1}^{\infty}{\frac{1}{1+2n}\:dn}=\lim_{a\to\infty}\left(\int_{1}^{a}{\frac{1}{1+2n}\:dn}\right)$. Using the substitution you mentioned $u=1+2n$, we have our lower bound as $u(1)=1+2(1)=3$ and our upper bound as $u(a)=1+2(a)=1+2a$.

We also have $\frac{du}{dn}=2\implies dn=\frac{du}{2}$, therefore we have:

$$\int_{3}^{1+2a}{\frac{1}{u}\frac{du}{2}}=\frac{1}{2}\int_{3}^{1+2a}{\frac{1}{u}\:du}$$

Taking our previous limit, we have:

$$\lim_{a\to\infty}{\left(\frac{1}{2}\int_{3}^{1+2a}\frac{1}{u}\:du\right)}$$

Which is what you have in your answer book.

$\endgroup$
1
$\begingroup$

Let $1 + 2x = u$ then $du = 2 dx \implies du = {1 \over 2} dx$

$x $ goes from $1$ to $\infty$, since we are using new variable $u$ here, it would have different bound. When $x \rightarrow \infty$, $ u \rightarrow \infty$ and when $x = 1$, $ u = 1 + 2 \cdot ( 1) = 3 $, so $u$ goes from $3$ to $\infty$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.